The Implementation of Uti Possidetis Principle in Determining Land Border Pole Point between Indonesia and Malaysia - Saru Arifin (Jurnal Hukum IUS QUIA IUSTUM, 2009)
In the era of independence, Indonesian territory covered all the former Dutch’s colony territory. The new state territory, which was based on the historical fact, is known as the uti possidetis principle. In the practical implementation, this concept is not problematic, especially in the border delimitation process. This article attempts to analyze the border demarcation mechanism between Indonesia and Malaysia land border. Furthermore, this article also attempts to discover the border demarcation impact to the state’s sovereignty in general and its impact to the local people mobility. The last, this article also attempts to know the border dispute settlement chosen by both Indonesia and Malaysia.Keywords: Border Sign, Souvereignity, The Border Region, Border Dispute, And Border Convention.